What has debt got to do with it? The Valuation of Homeownership in the Era of Financialization. Issue 1 (2nd January 2016) - Poppe, Christian; Collard, Sharon; Jakobsen, Turf Böcker
Abstract: Based on comparative focus group data from Norway, Denmark and England, this article asks why people take on substantial mortgages to become homeowners. It argues that financialization of the housing market has resulted in a widespread investment philosophy at the household level and changed the way people think and talk about "the home". High levels of mortgage borrowing have become commonplace and are justified by social valuations of owner-occupation based on beliefs around freedom through homeownership. Like previous research, the study shows that homeownership offers social identity, stability and belonging. But, this is wrapped up in an investor's language, such that the distinction between homes as socially valued living environments and homes as investment objects has become blurred. This makes it difficult – perhaps impossible – for households to assess the risks involved in home purchases.